GAMIFYING A MOOC : MOTIVATING LEARNERS - Ling, Nie Hui; Chen, Chwen Jen (2019)
Highlights: This study recommends a set of guidelines for choosing and incorporating motivating gamification elements into MOOCs. These guidelines are significant to MOOC designers and developers, particularly for those who intend to develop motivating gamified MOOCs.